ANALISIS TIME AND MOTION: EFISIENSI BEBAN KERJA DIRECT MARKETING DI ERA DISRUPSI DIGITAL - Asaretkha Adjane Annisawati; Imam Kambali; Rahmat Tri Yuli Yanto (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this research is to determine the sequence of Direct Marketing work processes before and after the Fourth Industrial Revolution. The Time and Motion Study method is used to assess the burden of Direct Marketing officers in all aspects of their duties in the Digital Disruption Era. This study's data was gathered through observations, interviews, and "Time and Motion" measurements. This study was carried out in the Direct Marketing departments of two different companies. According to the findings of this study, there are seven elements of the work sequence in the Direct Marketing work process from beginning to end. In addition, the total time required for the Direct Marketing work process after being disrupted by the digital era is 73 minutes 13 seconds, which saves 13 hours 17 minutes compared to before being disrupted